Modeling of Phonoelastic and Strain-stress Properties of ¹³C High Pressure Sensor for Use in Ecological Safety and Use of Natural Resources - Kondrat’yev, A.I. (Екологічна безпека та природокористування, 2009)
We investigate different properties of ¹³C diamond layer which was grown on a top of a brilliant cut diamond anvil. We connected equations of state for diamond with stress and strain concentrating on the case of [100], see ([1]) strain with diamond anvil bearing load plane as (100), (see [1]). We investigated the behavior of optical Г phonons with respect to pressure, strain and stress parameters. We also did simulation of these problems using finite element modeling and Nike2D computer software. We used O.H. Nielsen approach for modeling of the sensor. Досліджуються різноманітні властивості прошарку ¹³C-алмаза, який виростили на верхівці сенсора-діаманта. Поєднані рівняння стану алмаза і концентрації з фоноеластичними властивостями. Досліджуються рівняння, які описують поведінку оптичних фонів в термінах тиску і напруги. Проведено моделювання цих проблем з використанням методу кінцевих елементів і програмного забезпечення Nike2D. Для моделювання сенсору було застосовано метод наближення О. Нільсена. Исследуются различные свойства слоя ¹³C-алмаза, выращенного на вершине сенсора - бриллианта. Объединены уравнения состояния алмаза и концентрации с фоноэластическими свойствами. Исследуются уравнения, описывающие поведение оптических фононов в терминах давления и напряжения. Проведено моделирование этих проблем, используя метод конечных элементoв и программное обеспечение Nike2D. Для моделирования сенсора применен метод приближения О. Нильсена.